Patient activation among patients with type 2 diabetes and its association with perception of care, perceived autonomy support, sociodemographic and clinical characteristics - Muzlifa Mohamed Yusoff; Syahnaz Mohd Hashim; Norfazilah Ahmad (PLoS ONE, 2026)
Background Patient activation is an important aspect of self-management in type 2 diabetes (T2DM) and a key component of the Chronic Care Model, whereby patients should play an active role in their care. Past studies have yet to prove the exact factors influencing patient activation. Limited studies have examined patients’ perceptions of care and whether healthcare providers are autonomy-supportive. This study primarily focused on determining factors associated with patient activation, including sociodemographic and clinical characteristics, perception of care, and perceived autonomy support . Methods A cross-sectional study was conducted among T2DM patients at the public primary care clinic, Kepala Batas Health Clinic, Penang, the northern part of Malaysia, between 2 nd December 2024 and 30 th April 2025. Participants were sampled through a systematic sampling method and were given a self-administered questionnaire, comprising sociodemographic and clinical characteristics, Patient Activation Measure, Patient Assessment of Chronic Illness Care and Health Care Climate Questionnaire. Results A total of 450 patients participated, with a response rate of 85.3%. Many were Malay (92.9%), had lower income (99.0%), attained a secondary level of education (62.0%) and were on oral hypoglycaemic agents only (OHA) (66.0%). The mean patient activation score was 59.54 (SD 14.58), and 66.7% were at a high level of activation. Multiple linear regression revealed that factors significantly associated with patient activation were male (β = 1.984, [95% CI 0.629, 3.339], p = 0.004), age (β = −0.089 [95% CI: −0.161, −0.017], p = 0.015), HbA1c (β = −6.661 [95% CI: −7.022, −6.300), p < 0.001] and on OHA only (β = −1.460 [95% CI: −2.902, −0.019), p = 0.047]. Conclusions Patients tend to have lower activation when they are older, have higher HbA1c, and are on oral hypoglycaemic agents only. However, male patients exhibit higher activation. Interventions should focus on providing targeted, tailored support to those at risk of lower activation, to enhance their engagement in diabetes self-management and improve health outcomes.